Kaitan konduktivitas listrik dengan konsentrasi larutan garam dapur - Sapna Maharani; Suhadi Muliyono; Erlinda Ratnasari Putri (Progressive Physics Journal, 2022)
Research of the relationship between electrical conductivity and the concentration of table salt solution in several brands of table salt, namely brand A, brand B and brand C, has been done. Electrical conductivity () is used as the dependent variable, while concentration (C) is used as the independent variable. The concentration values are 0.1%, 0.2%, …, 0.7% for each brand of table salt. Measurements of electrical conductivity using a tool Conductivity Metertype pH/EC-983. Next, the average of the result of the measurements of electrical conductivity (σ ̅) are plotted against the concentration (C) of the table salt solution for the each brand of table salt, where each of the result is a straight line (linear) that it has a positive gradient/slope, that is σ ̅=(1360000C+694)µS/cm for brand A table salt, σ ̅=(1315300C+644)µS/cm brand B table salt and σ ̅=(1281700C+566)µS/cmfor brand C table salt. It seems that the gradient/slope of the straight lines in the various brands of table salt is almost the same, which it means that in general the content of ions in the various brands of legal table salt is relatively not much different. While the positive value of the gradient have the meaning that the higher the concentration of table salt solution, the higher the value of the electrical conductivity, which it is theoretically compatible with the physical concept.